1986
DOI: 10.1002/j.1460-2075.1986.tb04703.x
|View full text |Cite
|
Sign up to set email alerts
|

E. coli ribosomes with a C912 to U base change in the 16S rRNA are streptomycin resistant.

Abstract: Resistance to streptomycin (Sm) of Euglena gracilis chloroplasts can be due to a single C to T transition of the 16S rRNA gene in an invariant position which is equivalent to C912 of the Escherichia coli 16S rRNA. Since Euglena chloroplasts cannot be transformed we introduced, by site‐directed mutagenesis, a C912 to T transition in the cloned rrnB operon (pKK3535) of E. coli and used this new construct (pEM109) in transformation experiments. Transformed E. coli cells were selected for Sm resistance by colony p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 27 publications
4
45
0
2
Order By: Relevance
“…Streptomycin does not appear to bind to the S12 protein itself, but rather it binds to S12-deficient ribosomal core particles, and other proteins such as S3 and S5 are required (50). In E. coli, two streptomycin binding sites (positions 912 and 523) have been identified within 16S rRNA (36,38). Position 912 is adjacent to the S12 and S5 proteins, while position 523 is adjacent to the S4 protein (reviewed by Noller et al [39]).…”
Section: Discussionmentioning
confidence: 99%
“…Streptomycin does not appear to bind to the S12 protein itself, but rather it binds to S12-deficient ribosomal core particles, and other proteins such as S3 and S5 are required (50). In E. coli, two streptomycin binding sites (positions 912 and 523) have been identified within 16S rRNA (36,38). Position 912 is adjacent to the S12 and S5 proteins, while position 523 is adjacent to the S4 protein (reviewed by Noller et al [39]).…”
Section: Discussionmentioning
confidence: 99%
“…No variation in this composition was observed in oligonucleotide catalogs (about 400 species [48]), and the indicated C residue distinguishes eubacteria from archaebacteria and eucaryotes (42), all of which showed a U residue at this position (position 912). It has been reported that a mutation that changes this C residue to a U residue (in Escherichia coli) confers streptomycin resistance (20). The only known example of a C residue at this position among the naturally streptomycin-resistant archaebacteria occurs in Desulfurococcus mobilis, the only archaebacterium that is sensitive to streptomycin (R. Garrett, personal communication …”
Section: And Discussionmentioning
confidence: 99%
“…Despite this difference, streptomycin binds at the functional center of the ribosome in close proximity to the binding site of paromomycin. Tight binding of antibiotic is facilitated by interaction with nucleotides 13, 526, 915, and 1490 of 16S rRNA and protein S12 (45, 105,186,191,196). Like 2-deoxystreptamine-containing aminoglycosides, streptomycin induces misreading of the genetic code (142,143,250), but the underlying mechanism seems to be different.…”
Section: Mechanism Of Actionmentioning
confidence: 99%